2018
DOI: 10.1016/j.omtn.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA ZEB1-AS1 Was Suppressed by p53 for Renal Fibrosis in Diabetic Nephropathy

Abstract: The role of p53 in renal fibrosis is still controversial, and its underlying mechanisms remain not clear. Here, we showed that the pharmacological inhibition and genetic deletion of p53 in proximal tubular cells can attenuate renal dysfunction, tubular epithelial disruption, and interstitial fibrosis in db/db and STZ-induced diabetic nephrology (DN) mice. In human renal proximal tubule (human kidney 2 [HK-2]) cells, inhibition of p53 by PIF reduced the high glucose (HG)-induced extracellular matrix (ECM) accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 38 publications
0
50
0
Order By: Relevance
“…ZEB1-AS1 facilitated cell migration and metastasis via targeting heterogeneous nuclear ribonucleoprotein D0 (AUF1) to activate ZEB1 expression in bladder cancer (15). Another study hinted that ZEB1-AS1 played an anti-fibrotic role in diabetic nephropathy (16). Nevertheless, the mechanism of ZEB1-AS1 in EMT and renal fibrosis of diabetic nephropathy remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…ZEB1-AS1 facilitated cell migration and metastasis via targeting heterogeneous nuclear ribonucleoprotein D0 (AUF1) to activate ZEB1 expression in bladder cancer (15). Another study hinted that ZEB1-AS1 played an anti-fibrotic role in diabetic nephropathy (16). Nevertheless, the mechanism of ZEB1-AS1 in EMT and renal fibrosis of diabetic nephropathy remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Recently, it was shown that p53, ZEB1-AS1 and ZEB1 signaling may be involved in renal brosis in human DN. 10 However, the role and the molecular mechanism of ZEB1-AS1 in kidney brosis of human DN are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al reported that TGF-beta 1 can highly increase Erbb4-IR expression via a Smad3-dependent manner in the fibrotic kidney of mouse, suggesting that Erbb4-IR is a specific therapeutic target for chronic kidney disease [68]. Wang et al reported the lncRNA ZEB1-AS1 (zinc finger E-box binding homeobox1-antisense RNA 1) exerted an anti-fibrotic role in diabetic nephropathy [69]. Xie et al reported lncRNA H19 overexpression promoted renal fibrosis [70].…”
Section: Renal Fibrosis / Chronic Kidney Diseasementioning
confidence: 99%